The Relevance of Social Factors and The Fraud Triangle Model Factors in Detecting Academic Fraud in Accounting Student: Perceptions of Indonesian Millennials - Hana Norhamida (AKRUAL: JURNAL AKUNTANSI, 2025)
Introduction/Main Objectives: This study aims to test social factors and the fraud triangle model can be the basis for detecting fraud by accounting students in Indonesia. Background Problems: Indonesia is a country with a large number of public and private universities with accounting study programmes among ASEAN countries. But, the number of professional accountants currently available is still unbalanced when compared to the number of companies in Indonesia. Research Methods: This research when viewed from the analysis approach can be classified into the type of quantitative research. The data analysis that will be carried out in this study is to use a statistical approach consisting of descriptive statistics, classical assumption tests, model feasibility tests, and research hypothesis testing. Finding/Results: This research shows some important research results. First, the results of hypothesis testing show that the variables of pressure, opportunity, rationalisation, and social trust have a positive effect on behavioral intention to cheat. Second, the results of hypothesis testing show that the variables of pressure, opportunity, rationalisation, social trust, and behavioural intention to cheat have a positive effect on cheating behaviour. Third, the test results also show that pressure, opportunity, rationalisation, and social trust can lead to behavioral intention to cheat which in turn can lead to cheating behavior. Finally, the results of testing this hypothesis have not been able to prove the influence of subjective norms on behavioural intention to cheat and cheating behaviour.